DEVELOPMENT OF A PROJECT-BASED LEARNING MODULE ON LIGHT AND OPTICAL INSTRUMENTS TO ENHANCE STUDENTS’ CRITICAL THINKING SKILLS AND CREATIVITY - Kristin Oktaviani; Putut Marwoto; Siti Wahyuni (RADJA PUBLIKA, 2026)
This study aims to describe the development process, examine the validity, analyze user responses (teachers and students), and determine improvements in students’ critical thinking skills and creativity through the implementation of a science learning module based on Project-Based Learning (PjBL) integrated with deep learning on the topic of Light and Optical Instruments. This research employed a Research and Development (R&D) approach using a modified ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The trial participants consisted of 25 eighth-grade students from SMP Negeri 1 Pulau Malan. The findings indicate that: (1) the learning module was successfully developed in accordance with the ADDIE procedure, resulting in a 100-page instructional product; (2) the module met the “Highly Feasible” criteria based on expert validation by subject-matter and media specialists, with an overall mean validity score of 93.13%; (3) teacher and student responses were highly positive (teachers: 94.25%; students: 91.80%), indicating that the module is systematic and effective in supporting conceptual understanding; (4) there was a significant improvement in students’ critical thinking skills, as evidenced by an N-Gain score of 0.75 (high category); and (5) students’ creativity skills reached a very high category (91.50%) following module implementation, particularly in the dimensions of flexibility and originality, supported by the use of recycled materials in optical instrument projects. This study concludes that the PjBL-based learning module on Light and Optical Instruments is effective as an alternative instructional resource for strengthening students’ 21st-century skills.